1999
DOI: 10.1002/pdi.1960160307
|View full text |Cite
|
Sign up to set email alerts
|

Health professionals' perceptions of the seriousness of diabetes

Abstract: A cross‐sectional survey was undertaken to ascertain if health professionals rate the severity of NIDDM according to the treatment mode and to establish the reasons for their severity rating. A total of 421 responses were obtained. Most (70%), rated diabetes a serious disease, but there were significant differences in severity rating between the treatment modes, 69% rated insulin treatment serious, compared with 16% rating diet treatment serious (p<0.05). There was a trend for severity to be seen to increase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 13 publications
1
20
1
Order By: Relevance
“…8,18,23 Reasons for the low response rate were unclear but may be related to factors such as an increasing workload, frequently being asked to participate in research activities, or a fear of demonstrating diabetes knowledge deficits. 24 Other research conducted in similar populations derived similar demographic data, which suggests that the sample reflected the overall population in the study setting and this enhances its representativeness. 9,25 The PNs had received limited education about diabetes management and our findings suggest that their diabetes information could be out-dated.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…8,18,23 Reasons for the low response rate were unclear but may be related to factors such as an increasing workload, frequently being asked to participate in research activities, or a fear of demonstrating diabetes knowledge deficits. 24 Other research conducted in similar populations derived similar demographic data, which suggests that the sample reflected the overall population in the study setting and this enhances its representativeness. 9,25 The PNs had received limited education about diabetes management and our findings suggest that their diabetes information could be out-dated.…”
Section: Discussionmentioning
confidence: 84%
“…24 General practices and PNs are often the first point of care for people with diabetes. Thus, a PN's ability to screen for diabetes and provide health promotion and illness prevention messages in a timely way is important.…”
Section: Discussionmentioning
confidence: 99%
“…The U‐shaped lapse over time in risk awareness, with a change of focus from the baby’s to the mother’s health and her risk of developing type 2 diabetes, is possibly an effect of pregnancy being a transition to motherhood (Lundgren & Wahlberg 1999), and the regression could be related to the significant impact of GDM on the woman’s life as it is potentially life‐threatening (Lawson & Rajaram 1994), while the delivery of a healthy baby shows the opposite. Other factors that influence beliefs about health and illness are the perceived seriousness of the disease in health professionals (Dunning & Martin 1999) and the healthcare organisation (Hjelm et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular importance is the follow‐up six weeks after delivery, which should focus on GDM to develop an increased risk awareness of the condition being a risk marker for the development of type 2 diabetes. Beliefs held by health professionals about the seriousness of the disease are also important (Dunning & Martin 1999); they should not tell patients that GDM is transient to protect them against worries and negative emotions. The truth is important for developing realistic beliefs and positive health behaviour.…”
Section: Relevance To Clinical Practicementioning
confidence: 99%
“…Medical practitioners need to be aware that early screening, early diagnosis and early treatment of postprandial abnormalities can delay the onset of diabetes‐related complications, and are crucial to improving the quality of life and life expectancy of patients with type 2 diabetes [39]. A recent study that assessed the perceptions of health professionals towards diabetes demonstrated that many health professionals have a view of the severity of diabetes that is related to mode of treatment [43]. For example, 69% of health professionals in this study rated insulin‐treated type 2 diabetes as serious, compared with only 16% rating diet‐treated diabetes as serious.…”
Section: Management Of Type 2 Diabetes: the Key Playersmentioning
confidence: 99%